2013
DOI: 10.2176/nmc.53.195
|View full text |Cite
|
Sign up to set email alerts
|

Dural Arteriovenous Fistula at the Anterior Clinoid Process Draining Directly Into the Superficial Middle Cerebral Vein

Abstract: A 76-year-old man presented with subarachnoid hemorrhage. Selective angiography revealed a dural arteriovenous fistula (DAVF) at the right anterior clinoid process, draining into the superficial middle cerebral vein in a retrograde fashion. Two internal carotid artery aneurysms were also demonstrated at the origin of the posterior communicating artery and the anterior choroidal artery on the same side. The patient underwent craniotomy, and all lesions were treated simultaneously. Rupture of the anterior choroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Ruíz et al 64) reported a case of DAVF that developed in the LCS with a direct venous reflux into the SMCV. Ushikoshi et al 65) reported a DAVF near the anterior clinoid process draining directly into the SMCV with the varix. These two reported cases may be considered as DAVFs that developed in the lateral venous axis of the CS.…”
Section: Discussionmentioning
confidence: 99%
“…Ruíz et al 64) reported a case of DAVF that developed in the LCS with a direct venous reflux into the SMCV. Ushikoshi et al 65) reported a DAVF near the anterior clinoid process draining directly into the SMCV with the varix. These two reported cases may be considered as DAVFs that developed in the lateral venous axis of the CS.…”
Section: Discussionmentioning
confidence: 99%
“…The meningeal branches of the ICA included the ILT and the recurrent meningeal branch from the OphA ( Figure 3A ) ( 30 , 32 , 36 ). Sphenoid region DAVFs can recruit additional feeding arteries, such as the MHT, ethmoidal branch of the OphA, artery of the foramen rotundum, deep temporal artery, meningoorbital artery, superficial temporal artery, anterior auricular artery, and ascending pharyngeal artery ( 1–3 , 5 , 9 , 30 , 33 , 39–41 ). Even feeding arteries from the contralateral ICA and ECA can be recruited ( 40 , 42 ).…”
Section: Angioarchitecture Of Sphenoidal Region Davfmentioning
confidence: 99%
“…Sphenoidal region DAVFs are composed of sphenoid lesser or greater wing DAVFs (27)(28)(29). Sphenoid lesser wing DAVFs occur along the sphenoid ridge from the medially anterior clinoid process to the lateral pterion (Figure 2C) (5,(30)(31)(32). Sphenoid greater wing DAVFs include PCS and LCS DAVFs (Figure 2D) (24,33,34).…”
Section: Classificationmentioning
confidence: 99%
“… 1 2 There are 11 different pathological entities described so far on the ACP other than meningioma ( Table 1 ). 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33…”
Section: Background and Importancementioning
confidence: 99%